Islam dan Negara: Refleksi Gagasan Sekularisasi Nurcholis Madjid - Setiadi, Ozi; Aprilianti, Aeini Ahsani; Setyana, Ita; Yakin, Ahmad Ainul (POLITEA, 2020)
Islam and State: The Reflection of Secularization Idea of Nurcholis Madjid. There are some typologies of Islamic political thought. They are fundamental, secular, and liberal. Secular is the typology of Islamic political thought that separate religion and state. In the West, religion and state are differentiated. They advanced because of the separation of religion and state, but not in Islam. Nurcholis Madjid is one of the Islamic political thinkers who explains the secularization of religion and the state. The purpose of this study is to analyze the thoughts of Nurcholis Madjid about the secularization of Islam and the state. This research uses descriptive analytical method. According Madjid the answers of modernization problems especially among the Indonesian Muslim community is secularization. Secularization is needed because Moslem cannot differentiate religion (din) and state (dawlah). Secularization is carried out for Moslems who “deify the world” which should be worldly, and give up religious matters. The formation of an Islamic state is the failure of Moslems to respond to the problem of modernization.